Anisotropy of the grain size effect on the electrical resistivity of n-type Bi1.9Gd0.1Te3 thermoelectric textured by spark plasma sintering. Issue 9 (August 2020) - Ivanov, Oleg; Yaprintsev, Maxim; Vasil'ev, Alexei
Highlights: Textured Bi1.9 Gd0.1 Te3 compounds with various grain structures were SPS-prepared. Grain size is different for directions, parallel and perpendicular to SPS-pressing. Properties of fine- and coarse-grained samples can be combined in textured samples. Anisotropy of grain size effect in electrical resistivity due to texturing was found. Abstract: Spark plasma sintering (SPS) was applied to prepare textured Bi1.9 Gd0.1 Te3 compounds with various grain structures, tuned by changing in the sintering temperature. The grains forming ordered lamellar structure under texturing are elongated in plane oriented perpendicularly to SPS-pressing direction. As result, average grain size measured parallel to this direction and corresponding to fine-grained samples happened to be much less as compared to relevant size for perpendicular direction characteristic for coarse-grained samples. Anisotropy in electrical resistivity inherent for single crystal was found to be partially recovered in textured samples, i.e. resistivity measured along directions parallel or perpendicular to SPS-pressuring direction is different. Moreover, resistivity for both directions is increasing with decreasing in grain size or with decreasing in intergrain distance. Grain size effect on resistivity due to grain boundary scattering of electrons was found to be anisotropic, since the effect is observed for different ranges of change in average grain sizes.